Anticipated Versus Actual Emotional Reactions to Disclosure of Results of Genetic Tests for Cancer Susceptibility: Findings From p53 and BRCA1 Testing Programs - Dorval, Michel; Patenaude, Andrea Farkas; Schneider, Katherine A.; Kieffer, Stephanie A.; DiGianni, Lisa; Kalkbrenner, Kathy J.; Bromberg, Jonas I.; Basili, Laura A.; Calzone, Kathleen; Stopfer, Jill; Weber, Barbara L.; Garber, Judy E. (Journal of clinical oncology, 2000)
PURPOSE: We examined the ability of individuals undergoing genetic testing for cancer susceptibility in two structured research protocols to accurately anticipate emotional reactions to disclosure of their test result. We explored whether accuracy of emotional anticipation was associated with postdisclosure psychologic adjustment. METHODS: Data from 65 individuals were analyzed; 24 members of Li-Fraumeni cancer syndrome families were tested for p53 mutations (all 24 were unaffected), and 41 subjects with hereditary breast-ovarian cancer susceptibility were tested for BRCA1 mutations (34 were unaffected and seven were affected). Subjects were from families in which a germline mutation had been previously identified. At the pretest session, subjects rated the extent to which they anticipated feeling each of six emotional states (relief, happiness, sadness, guilt, anger, and worry) after disclosure that they did or did not carry the familial mutation. After receiving their test result, they rated their feelings on the same scale of emotions for the appropriate condition. Extent of accuracy and association with psychologic distress at 6 months, as assessed with standardized measures, were evaluated. RESULTS: Overall, mean levels of emotional reactions after receiving test results were not different from those anticipated before result disclosure. However, affected BRCA1 carriers experienced higher levels of anger and worry than they had anticipated. Underestimation of subsequent distress emotions related to test result was associated with a significant increase in general psychologic distress at 6 months. CONCLUSION: Unaffected individuals in cancer-predisposition testing programs are generally accurate in anticipating emotional reactions to test results. However, cancer patients may underestimate their distress after disclosure of positive results and could benefit from intervention strategies.